Control-Ownership Wedge and Industry Specialist Auditor - Aree Saeed Mustafa (Master of Accounting Universitas Trunojoyo Madura, 2021)
This study extends agency theory by explaining the client's understanding of audit quality. This study contributes to the audit literature by examining the effect of wedge control-ownership on industry specialist auditors that have not been researched in Turkey. The interests of minority and controlling shareholders are not completely compatible. The research analysis method used a logistic regression model, finding that firms that practice a larger difference between control rights and cash flow rights tend to prefer high audit quality measures by industry specialist auditors. This study encourages regulators to improve law enforcement to enhance the role of corporate governance in Turkey to address the features of ownership-control firms and offer a suitable environment for investment and minority shareholders.